Subjective Semantics of Representations of Creativity in Psychology Cadets - Oksana G. Korneva; Mehirban M. Abdullaeva; Valentina V. Barabanshchikova (Lomonosov Moscow State University, 2024)
Background. The necessity of studying perceptions of creativity in psychology cadets is conditioned by the fact that the "soft" skill of creativity is associated with the ability to go beyond the given conditions and to act effectively in uncertain situations, and also by the fact that the successful adaptation of a young specialist to work depends on whether his perceptions of his activity coincide with its real content. Objectives. The research is meant to identify the peculiarities of representations of creativity in psychology cadets at the adept stage. Study Participants. A total of 201 people (122 men and 79 women) participated in the study, including representatives of different professions: working professionals and trainees, students and cadets. The average age of the sample was 31 years. Methods. Psychosemantic methods were used in the study: group associative experiment and card sorting method. They allow to construct a subjective semantic space reflecting the peculiarities of perceptions of creativity. Results. As a result of the associative experiment, a list of 86 frequent words describing professional activity was obtained. Sorting of the obtained 86 words by cadet psychologists, psychology students, and psychologists of the scientific platoon revealed significant differences in the content and structure of representations of creativity. Comparison of the semantics of creativity in psychologists at the adept stage shows that university students have a more complex structure of representations in comparison with cadets, connected with the allocation of a separate cluster "hobby, interest, development" and at the same time similar in content to the representations of working psychologists on the proximity of "labor, work" with creativity. At the same time, the similarity of clusters in the description of creativity by students and cadets indicates that the ideas about it are laid down at the early stages of professional training. Conclusions. Reconstruction of subjective semantics of creativity by the method of semantic spaces in psychology cadets is a promising qualitative description method for specific characteristics of professional activity.